The Environment-Based Supplementary Reading Materials for Junior High School Students - Azizah, Dinar Martia; Sugirin, Sugirin (Journal of Interdisciplinary Studies in Education, 2019)
One such effort toward this is the development of environment-based supplementary reading materials for students. In accordance with this, the objectives of this research are: 1) to investigate the need of junior high school students for environment-based supplementary reading materials; and 2) to develop environment-based supplementary reading materials suitable for these students. The subjects of this research and development were eighth grade students of a junior high school. The procedure utilized is a modified version of the research and development steps proposed by Borg & Gall and included four development procedures. The stages of this modified procedure were: 1) the exploration stage, including need analysis; 2) the prototype development stage, including planning and developing the format/draft; 3) the revision stage, using expert evaluation; and 4) the finalization stage. The resulting supplementary reading material has been developed into 3 units, with the texts being recount, descriptive, and narrative. Each unit consists of a list of new vocabulary, a comic, a main text, and exercises. The exercises at the end of each unit have the purpose of confirmation.The texts aim to convey an ideal relationship between humans and environment.